Cd and Feconcentrationin the liver, kidney and bone of Notopterusnotopterusfrom the downstream of the Sail River, Pekanbaru - Annisa Rahmah; Budijono Budijono; Muhammad Hasbi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abstract Sail River has been polluted by heavy metals and those may affects the organs of aquatic organisms, including Notopterus notopterus. To understand the Cd and Fe content in the livers, kidneys and bones of the fish, a study has been conducted on January to February 2018.Samplings were conducted two times, once/month, in the downstream of the river. The fish samples were obtained from fishermen. Heavy metals content were analyzed using AAS.Results shown that the concentration of Cd in liver, kidney and bone were 1.178;0,956 and0,698 mg/kg,whilethose of the Fe were 1,131;1,177 and 0,948 mg/kg respectively. Data obtained indicate that the fish from the downstream of the Sail River were already contaminated with Cd and Fe. Keywords:cadmium, iron, aquatic organism, fish organ